Advancing the synthesis and reactivity of aza-sulfur functional groups - Tilby, M (2021)
The work described herein documents several key advances in the field of aza-sulfur chemistry. Aza-sulfur chemistry encompasses a broad range of functional groups, where within this report, a particular focus has been placed on sulfoximines, sulfonimidamides and sulfonamides. In order to advance the synthesis and reactivity of these molecules a variety of projects have been undertaken, both using computational and experimental methods. On the account of these studies several key contributions to the field have been made and these will be outlined in the following chapters.